2011
DOI: 10.1111/j.1742-1241.2011.02693.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and detection rate of underlying disease in men with erectile dysfunction receiving phosphodiesterase type 5 inhibitors in the United Kingdom: a retrospective database study

Abstract: Summary Aim:  To determine the rate of newly detected underlying disease in men receiving their first (index) phosphodiesterase type 5 inhibitor (PDE5i) prescription. Methods:  This non‐interventional, retrospective study used anonymised patient records from UK general practices identified from the THIN database. Records of men aged ≥ 18 years, who received an index PDE5i prescription between January 1999 and June 2008 and with a continuous medical history (≥ 60 months) before the index prescription were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…However, the prevalence of depression (9.1% and 11.1%) was somewhat higher than that in this study (7.0%). Consistent with the present results, the prevalence of comorbid conditions was significantly higher in men with ED than in men without ED . Multivariate analysis estimated that the risk of diabetes, hypertension and depression were increased, overall and across age groups …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the prevalence of depression (9.1% and 11.1%) was somewhat higher than that in this study (7.0%). Consistent with the present results, the prevalence of comorbid conditions was significantly higher in men with ED than in men without ED . Multivariate analysis estimated that the risk of diabetes, hypertension and depression were increased, overall and across age groups …”
Section: Discussionsupporting
confidence: 90%
“…The results of this study were generally consistent with previously published results of real‐world observational data. Previous studies have assessed the prevalence of underlying comorbidities in men with ED using data from US health insurance claims databases and in men from a UK general practice EHR database . The age distribution of the men was not reported in the UK study, but the reported age distribution of men with ED in the US studies (5%‐7% aged ≤35 years; 16%‐17% aged 36‐45 years; 34%‐36% aged 46‐55 years; 34%‐36% aged 56‐65 years; 5%‐7% aged 66‐75 years; and 2% aged ≥76 years) was broadly similar to that of this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, we also diagnosed unknown cardiovascular or metabolic disorders in 24% of our ED subjects (Figures 2 and 3). These numbers are nearly double those reported in a recent UK study [37], where the rate of discovery of previously unknown conditions was 11.53%. The discrepancy is likely due to methodological differences, rather than regional characteristics.…”
Section: Discussionmentioning
confidence: 48%
“…Although we did not use a questionnaire to assess for ED symptoms, that method can be subject to desirability bias, and medication use is a more objective method to characterize ED. Prior studies have likewise utilized the prescription of phosphodiesterase inhibitors as a proxy for the presence of ED …”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have likewise utilized the prescription of phosphodiesterase inhibitors as a proxy for the presence of ED. 7,8,24 Alternatively, our sample may be confounded by a treatment bias, as patients who are healthier and have higher socioeconomic status may be more likely to undergo treatment for ED. The men in our sample were also relatively fit, with the average participant able to achieve 10.2 METs.…”
Section: Discussionmentioning
confidence: 99%